Residualidade Medieval em Aluísio Azevedo: Um Estudo do Medo e da Culpa no Romance o Homem - Rodrigues, Isabel Guimarães (2010)
The present work aims at analyzing medieval residuality in the naturalistic novel O Homem (The Man) by Aluísio Azevedo. We can point out some characteristics of the medieval mentality throughout the narrative, mainly when it refers to religiosity, fear and guiltiness of sin. Middle Age culture and laws are deeply based on religiosity through the Catholic Church Christian-Jewish Dogmas. They retain the power of leading the daily society through the sacramental system and religious routine and also feel free to judge and condemn people considered sinful and ungodly. Power based mechanism was used to manipulate and control people’s thoughts and attitudes. Residual constancy of the medieval mental cultural heritage found in the O Homem, turns out to be relevant in the Occident mindset. And to perform this link between Middle Age and the novel we will focus on the Residual Theory, by Roberto Pontes, which consists of the residue of one mentality into another mentality within culture or literature. We intend to develop the theory from the point of view of the History of Mentalities, one of the guidelines of the theory, as well as explain cultural hybridization, crystallization and residual concepts. We will also focus on the role of the Catholic Church in the Middle Age society to finally analyze the novel within the idea of the original sin, devilry and vampirism.